2016
DOI: 10.1155/2016/9761697
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress Markers and Their Dynamic Changes in Patients after Acute Ischemic Stroke

Abstract: We have focused on determining the range of oxidative stress biomarkers and their dynamic changes in patients at different time points after the acute ischemic stroke (AIS). 82 patients with AIS were involved in our study and were tested: within 24 h from the onset of the attack (group A); at 7-day follow-up (group B); and at 3-month follow-up (group C). 81 gender and age matched volunteers were used as controls. Stroke patients in group A had significantly higher concentrations of plasma lipid peroxides and u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 23 publications
2
40
0
4
Order By: Relevance
“…Paspalj et al [3] point out that the levels of catalase demonstrated a slight increase in patients who did not survive, but no statistical relevance was verified. But for Žitnanova [5], there was a statistically significant increase in catalase levels, especially on the seventh day. In another aspect, Chen et al [12] comprehend thiol as a relevant biomarker for the measurement of increased oxidative damage.…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations
“…Paspalj et al [3] point out that the levels of catalase demonstrated a slight increase in patients who did not survive, but no statistical relevance was verified. But for Žitnanova [5], there was a statistically significant increase in catalase levels, especially on the seventh day. In another aspect, Chen et al [12] comprehend thiol as a relevant biomarker for the measurement of increased oxidative damage.…”
Section: Resultsmentioning
confidence: 89%
“…However, Žitnanova [5] produced a sample with a statistically significant elevation of SOD in larger quantities on the seventh day after stroke onset. It could be construed as an adaptive response of the organism to pre-ischemic conditioning.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It catalyzes the decomposition reaction of H2O2 to water and molecular oxygen (7). Although numerous studies point to the increased production of ROS in AIS, the results of antioxidant enzymes activities in this disease are contradictory (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%